2000
DOI: 10.1177/004051750007000612
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat and Moisture Transport in Fabrics and Garments Determined with a Vertical Plate Sweating Skin Model

Abstract: A vertical sweating skin model is developed and changes in vapor pressure within a clothing system are measured to investigate the effects of fiber type, air layer thickness, and garment openings on the microclimate. Cotton broadcloth, polyester broadcloth and cotton canvas are considered. Openings of a garment, such as neck, armhole and waist, are simulated, and the total openness is controlled at 0, 10, 20, 40, and 60%. To evaluate changes in the microclimate of the clothing system, a buffering index Kd and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 13 publications
0
30
0
2
Order By: Relevance
“…This air acts as an insulator preventing heat transfer by conduction and radiation. Yoo et al (2000) found that the thickness of the air layer is negatively correlated with the vapour pressure, which affects the wearer's comfort. Likewise, previous research has demonstrated that the R ct and R et measurements improve when the air gap is considered (Gibson, 1993).…”
Section: Testing Conditionsmentioning
confidence: 99%
“…This air acts as an insulator preventing heat transfer by conduction and radiation. Yoo et al (2000) found that the thickness of the air layer is negatively correlated with the vapour pressure, which affects the wearer's comfort. Likewise, previous research has demonstrated that the R ct and R et measurements improve when the air gap is considered (Gibson, 1993).…”
Section: Testing Conditionsmentioning
confidence: 99%
“…The effect of moisture on the transfer properties (such as heat and water vapour) of clothing systems at lower temperature (21-35°C) has been extensively investigated and the mechanism is well known (Farnworth 1986;Gibson 1993;Parsons 1994;Weder et al 1996;Yoo et al 2000;Fan and Chen 2002). However, this phenomenon is rather complex when fire-fighting is considered as it involves high temperature.…”
Section: Protection and Fire-fighter's Clothingmentioning
confidence: 99%
“…Comfort is basic and universal need of human being and presents one of the most important aspects of clothing. During clothes wearing, heat and humidity produced by body has been stopped as layers of air before passing in the environment, resulting in characteristic microclimate between skin and clothing, defined as the feeling of comfort (Yoo et al, 2000;Grujić et al, 2010). Thermal effects largely contribute to the comfort of the individual, whereby a complex physiological and psychological factors together with clothes play an important role in defining the complex phenomenon of comfort (Andreen et al, 1953).…”
Section: Introductionmentioning
confidence: 99%